MANFAAT ULTRASOUND THERAPY DAN MOBILISASI SARAF TEKNIK ULTT 1 PADA KASUS CARPAL TUNNEL SYNDROME : STUDI KASUS: MANFAAT ULTRASOUND THERAPY DAN MOBILISASI SARAF TEKNIK ULTT 1 PADA KASUS CARPAL TUNNEL SYNDROME : STUDI KASUS - Sri Fitri Purnawati; Sugiono; Aditya Johan Romadhon (Jurusan Fisioterapi Poltekkes Kemenkes Surakarta, 2024)
Background: Carpal Tunnel Syndrome (CTS) is a common problem in the upper extremities caused by compression of the median nerve that passes through the carpal tunnel at the wrist. If the median nerve is compressed or pinched, it will cause tingling, numbness, and sometimes pain in the part affected by the nerve. To overcome this problem, physiotherapy procedures were carried out in the form of ultrasound and ULTT 1 nerve mobilization. Objective: to determine the benefits of ultrasound and ULTT 1 nerve mobilization in CTS cases. Method: This research is a case study, patients diagnosed with CTS were given therapy using modalities in the form of ultrasound and ULTT 1 nerve mobilization with 5 repetitions for 2 sessions totaling 3 times. Results: The results obtained from measuring the functional ability of the hand were from 20% (minimum disability) to 16% (minimum disability). Conclusion: after physiotherapy was carried out on Mrs. K, 53 years old, diagnosed with carpal tunnel syndrome using ultrasound modality and ULTT 1 nerve mobilization, found an increase in hand functional ability using WHDI from 20% (minimum disability) to 16% (minimum disability).